Pengaruh Bonus, Ukuran Perusahaan, dan Leverage pada Manajemen Laba - Tia Deviyanti, Ni Wayan; Sudana, I Putu (E-Jurnal Akuntansi; Vol 23 No 2 (2018)DO - 10.24843/EJA.2018.v23.i02.p23, 2018)
The purpose of this study is obtain empirical evidence about the effect of bonuses, firm size, and leverage on earnings management. The study was conducted on food and beverage companies listed in BEI in 2014-2016. Sampling method used is nonprobability sampling method with purposive sampling technique. There are 15 companies as a sample with a total of 45 observations. Data collection is done by documentation method. Technique Data analysis used is multiple linear regression test. Based on the results of the analysis, found that bonuses have no effect on earnings management, firm size negatively affect earnings management, and leverage positively affects earnings management. The theoretical implications in this study confirm the agency theory and positive accounting theory. Practical implications in this study of companies to strengthen internal firm and investor caution in making decisions in investing, in order to see the ratio of corporate health, because viewed from a high leverage can improve earnings management. Keywords : Bonus, firm size, leverage, earnings management and food and beverage.